FRI0025 The tam receptors axl and mer play a protective role in a temporal and spatial manner in inflammatory arthritis. (15th June 2017) - Waterborg, CEJ; Través, PG; Beermann, S; Koenders, MI; Lent, PLEM van; Hoogen, F den; Kraan, PM van der; Loo, FAJ van de
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by an inflammatory response in synovial joints. One family of tyrosine kinase receptors that mediates a natural anti-inflammatory feedback mechanism are Tyro3, Axl and Mer (gene Mertk ; TAM). The two principal TAM receptor protein ligands are Growth Arrest-Specific 6 (Gas6) and Protein S (Pros1). Targeting the TAM receptors by adenoviral overexpression of their ligands alleviates experimental arthritis pathology. Notably, Gas6 is a ligand for all three receptors but with the highest affinity for Axl. In contrast, Pros1 can only activate Tyro3 and Mer but not Axl. The role of the separate TAM receptors in RA has not been elucidated. Objectives: To reveal the individual role of the TAM receptors Axl and Mer in an experimental inflammatory model of RA. Methods: The KRN serum transfer model of arthritis was induced by two intraperitoneal injections of arthritic K/BxN serum in Axl -/-, Mertk -/-, Axl -/- Mertk -/- and wild-type (WT) mice. Ankle joints were macroscopically scored for 7 days. At day 0, 2 and 7, ankle and knee joints were isolated for histology and immunohistochemistry. Results: The course of arthritis was studied macroscopically and Mertk -/- mice had increased macroscopic ankle scores until day 4, compared to WT. Thereafter, Axl -/- mice developed more severe arthritis as compared to WT with enhanced macroscopic scores from day 4 until day 7. Histology of ankle joints showed significantly more inflammation in Mertk -/- mice at day 2 and increased arthritis pathology in Axl -/- mice at day 7, reflecting the macroscopic ankle scores. Histological analysis of ankle joints of Axl -/- Mertk -/- mice at day 7 showed enhanced pathology compared to both Axl -/- and WT mice, indicating an additive effect of Axl and Mer deficiency. In contrast to the ankle joints at day 7, enhanced macroscopic scores and arthritis pathology in knee joints of Mertk -/- mice, compared to WT mice, was observed at both day 2 and day 7. Axl -/- mice had comparable knee joint pathology compared to WT. To explain the discrepancy of Axl involvement between ankle and knee at day 7, we examined Axl expression in synovium before the onset of arthritis. The cells in the lining layer of ankle synovium were strikingly Axl positive whereas the synovium of the knee joints was Axl negative. Conclusions: The Mer receptor plays a protective role at the onset of arthritis whereas the Axl receptor takes over this role in established disease in ankle joints. In the knee joints, however, Mer but not Axl, plays a prominent protective role, likely due to the lack of Axl in naïve knee joints. These findings identify the TAM receptors Axl and Mer as protective in arthritis, dependent on the distinct anatomic location. It is tempting to speculate that these differences in topographically distinct synovial joints could, at least in part, explain the differential joint involvement in RA. Disclosure of Interest: None declared